The feasibility of radical cystectomy in elderly patients - Görgel, Sacit Nuri (Turk J Urol, 2014)
OBJECTIVE: In this study, we aimed to investigate the relationship between age and tumor characteristics and to evaluate oncologic results after radical cystectomy in bladder cancer with respect to age. MATERIAL AND METHODS: We reviewed 460 patients retrospectively who underwent radical cystectomy. Patients were divided into two groups according to age: ≥70 (Group 1), and <70 (Group 2). We compared tumor pathological characteristics and the results of long-term follow-up in both groups. The first group included 76 (16.7%), and the second group 379 (83.3%) patients. The mean age of the patients was 73.3±3.01 years (70–85) in Group 1 and 58.3±7.47 years (34–69) in Group 2. The American Society of Anesthesiologists (ASA) score was less than three in all of the patients, and there was no risk for major surgery. RESULTS: No statistically significant difference was found between groups with respect to pathological T stage (p=0.567), lymph node involvement (p=0.179), or histological grade (p=0.567). Perioperative mortality rates were 3.9, and 3.4% in groups 1 and 2, respectively (p=0.218). Perioperative complication rates were 14.7, and 17.5% for groups 1, and 2 respectively (p=0.578). Five-year disease-specific survival (DSS) rates were 57.0, and 51.6% Groups 1, and 2, respectively. The mean DSS periods were 82.05±4.88 and 71.68±8.53 months for Groups 1, and 2, respectively. Five-year overall survival rates were 43.9% for Group 1 and 45.9% for Group 2. The mean overall survival times were 54.02±8.47, and 69.25±4.97 months for Groups 1, and 2, respectively. In Cox regression analysis, tumor stage (p=0.012) and lymph node involvement (p<0.001) were significant factors that affected the survival in both groups. None of the patients received neoadjuvant radiotherapy or chemotherapy. CONCLUSION: We found that oncological outcomes of radical cystectomy performed with the indication of bladder tumor were comparable between young and elderly. We believe that age per se should not constitute a contraindication for radical cystectomy operations.